Comparative anatomy and phylogenetic importance of the branchial musculature in sharks of the superorder Galeomorphi (Chondrichthyes:Elasmobranchi) - Oliveira, Lucas Romero de (2018)
The present work consists of an anatomical comparison of the branchial musculature of galeomorph groups in order to search for evidence that could indicate possible phylogenetically relevant patterns, especially related to the Heterodontiformes and other families within the orders of Galeomorphi. Previous studies based on other muscle complexes have contributed with information that helped to address thoses questions (Datavo & Vari, 2014; Soares & Carvalho, 2013a,b). Nine branchial muscles of 44 species among all galeomorph orders, 13 species from two of the five recognized squalomorph shark orders (Squaliformes and Hexanchiformes) and one batoidean were observed, totalizing 57 species. The results indicate a highly conserved anatomy on this anatomical complex, possibly indicating a conservative generalized condition at both chondrichthyan and gnathostomes level. The most informative muscles in this context were the m. trapezius, the m. adductores arcuum branchialium, the m. coracobranchiales, especially the portion associated with the last branchial arch, and the m. arcuales dorsalis. The other five muscles have little to no variation among different groups. The analysis of the muscular patterns indicates that lamniforms and carcharhiniforms are sister-groups and Orectolobiforms and Heterodontiforems are sister-groups, supported by the m. trapezius having a single ramus and absence of the insertion onto the epibranchial only in Orectolobiformes and Heterodontformes, as well as the fifth m. coracobranchialis has its fibers oriented forward, when opposed to two rami in the m. trapezius in all other orders and fibers of the fifth m. coracobranchialis either upwards or obliquely organized. Regarding carcharhiniform and lamniform relatioships, the muscles that provide evidence are the presence of a second ramus on the fifth m. coracobranchialis, with a single ramus in all other orders, the crescent shape of the m. adductores arcuum branchialium, with triangular shape in other groups, and the presence of a raphe between the antimeres of the m. constrictores branchiales superficiales, which are triangular outside this group. Also, it was found support for the division of shark groups between Galeomorphi and Squalomorphi with the presence of a posterior ramus on the m. arcuales dorsalis in squalomorph sharks